A safe and fast-charging lithium-ion battery anode using MXene supported Li3VO4. Issue 18 (16th April 2019) - Huang, Yanghang; Yang, Haochen; Zhang, Yi; Zhang, Yamin; Wu, Yutong; Tian, Mengkun; Chen, Peng; Trout, Robert; Ma, Yao; Wu, Tzu-Ho; Wu, Yuping; Liu, Nian
Abstract : An innovative anode material of lithium-ion battery, Li3 VO4 /Ti3 C2 T x, was synthesized. The overall three-dimensional electronic and ionic transport pathways were formed in anode, which promoted both electron and ion transport during the lithiation and delithiation processes. Abstract : During fast charging, the commonly used Li-ion battery anode material, graphite, has a significant shortcoming, that is, its discharge potential is too low to guarantee the safety of batteries. Li3 VO4 (LVO), an alternative anode material, has a safe discharge potential window of 0.5 V to 1.0 V vs. Li + /Li and high theoretical capacity (∼394 mA h g −1 ). However, the poor conductivity of LVO (∼10 −10 S m −1 ) constrains its further applications. In this paper, we innovatively embedded uniform LVO onto a multilayered material, Ti3 C2 T x MXene, by a sol–gel method. The Ti3 C2 T x MXene nanolayers with high electrical conductivity (2.4 × 10 5 S m −1 ) served as a scaffold to load LVO nanoparticles. The LVO/Ti3 C2 T x MXene composite exhibited remarkable electrochemical performance in terms of rate capability and long-term cycle stability in comparison with bare LVO and commercial graphite anodes. The LVO/Ti3 C2 T x MXene composite delivered an initial capacity of ∼187 mA h g −1 and 146 mA h g −1 after 1000 cycles at 5C, compared to bare LVO (an initial capacity of ∼41 mA h g −1 and ∼40 mA h g −1 after 1000 cycles at 5C) and graphite (∼71 mA h g −1 after 1000 cycles at 5C). This work opens new possibilities of anode materials for safe and fast-charging Li-ion batteries.